The massive sulphides and magnetite deposits of northern Ethiopia - Hamrla, Milan (Geologija, 1978)
The massive sulphides of northern Ethiopia occur within the Upper Precambrian eugeosvnclinal sequence locally known as the Tsaliet and Tambien Groups belonging to the Red Sea Proterozoic basin. The geotectonic history of the basin is interpreted as a cratonised island are. The age of the sequence is in the order of 1,000 Myr. The early sodic extrusive-intrusive rocks were followed by peralkaline granitoides. The primary mineralisations originated in submarine conditions by volcanic exhalative-sedimentary processes. Sulphide and oxide iron facies coexist, both on a regional as well as on a micoroscopic scale. Later hydrothermal episodes affected the deposits and rearranged and enriched the ore minerals. The altered enclosing rocks display greenschist facies metamorfphism, whereas the ore minerals and ore texture seem to be little affected. The massive sulphide deposits fit well with the Pb-Zn-Cu-Ag proterozoic type, with zine and copper strongly prevailing over lead, the metal tenors variable and generally very low.